2021
DOI: 10.1212/nxi.0000000000001052
|View full text |Cite
|
Sign up to set email alerts
|

International Consensus Recommendations for the Treatment of Pediatric NMDAR Antibody Encephalitis

Abstract: ObjectiveTo create an international consensus treatment recommendation for pediatric NMDA receptor antibody encephalitis (NMDARE).MethodsAfter selection of a panel of 27 experts with representation from all continents, a 2-step Delphi method was adopted to develop consensus on relevant treatment regimens and statements, along with key definitions in pediatric NMDARE (disease severity, failure to improve, and relapse). Finally, an online face-to-face meeting was held to reach consensus (defined as ≥75% agreemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
102
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 60 publications
4
102
0
6
Order By: Relevance
“…Neurological autoimmune diseases have increasingly being treated with TA. This is in accordance to international guidelines in which TA is recommended in pediatric autoimmune encephalitis early in severe disease manifestation ( 11 ).…”
Section: Discussionsupporting
confidence: 83%
“…Neurological autoimmune diseases have increasingly being treated with TA. This is in accordance to international guidelines in which TA is recommended in pediatric autoimmune encephalitis early in severe disease manifestation ( 11 ).…”
Section: Discussionsupporting
confidence: 83%
“…Nepal et al ( 99 ) found rituximab was effective for treatment of AE with an acceptable toxicity profile, while Lee et al ( 100 ) found that high doses of rituximab showed benefits in refractory AE patients. The international consensus ( 101 ) recommended rituximab for cases refractory to the first-line agent in both anti-NMDAR AE children and adults, while cyclophosphamide was suggested 1–3 months after second-line initiation. As the cases included in these three studies above were mostly anti-NMDAR AE, the results did not exactly match our research.…”
Section: Discussionmentioning
confidence: 99%
“…To sum up, the timing of upgrade to third-line therapy is very challenging and clinicians need to balance the risk of severe disease with the risk of treatment side effects ( 102 ); third-line therapy still provides a therapeutic option for patients with refractory AE and has shown beneficial results in some of the case reports or cohort studies listed in the current study. With ever-growing attention on refractory AE, we can expect that future studies could potentially elucidate these problems and find more effective therapies for AE.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%